The relationship between depression, anxiety and stress with work-life balance among military personnel - Khairol Anuar, Farah Natasha Aliya; Mohamad Yusop, Yusni; Zainudin, Zaida Nor; Wan Othman, Wan Norhayati (Human Resource Management Academic Research Society, 2024)
The blurring of boundaries between one's professional and personal lives makes it difficult to find a balance in military life. Hence, the purpose of the study was to determine whether there is a connection between work-life balance and mental health issues such depression, anxiety, and stress. The relationship between the independent and dependent variables can be found using Pearson's Correlation. The research includes 293 individuals from Army Headquarters. The relationship between work-life balance and mental health symptoms including anxiety, stress, and depression was examined using two instruments: the DASS-21 and a work-life balance questionnaire. Military personnel's levels of depression (r = 672, n = 293, p =.000), anxiety (r =.594, n = 293, p =.000), and stress (r = 663, n = 293, p =.000) are moderately strong correlated with their work-life balance.